Desarrollo de una aplicación web progresiva para la planificación de atención y soporte corporativo en la empresa Evolution Soft - Gómez Molina, Alex Paul (2022)
Evolution Soft company was created in 2017, it is located in the Pichincha province and it is dedicated to carrying out projects related to software development, computer security and business intelligence, over the years it has obtained a considerable portfolio of clients in different parts of Ecuador, which is why they must keep in continuous contact with all the companies that have acquired any of their products or services to provide them with attention or support when they require it. However, these processes are carried out through the use of general purpose tools such as spreadsheets, email, Word files or telephone calls that prevented planning, coordinating and monitoring the attention and technical service that is being offered to customers clients, which is why their dissatisfaction is noted since on many occasions there have been delays or postponement of meetings due to the poor distribution of work in the company. Faced with this problem, the development of a PWA (Progressive Web Application) is proposed, capable of being installed on any operating system platform through which the processes related to the attention and corporate support that the company provides to its clients are automated, taking as reference ITIL v4, for the development, software tools have been used that can operate on the technological infrastructure of the company, in addition to following the Scrum framework with the intention that the process required for the implementation of the system follows the most appropriate methodological elements for the benefit of creating functional software for the beneficiary institution.